Prevalence of S.typhi in Blood Cultures-Antimicrobial Sensitivity and incidence of ESβLs in MDR Isolates - Khalid Mahmood ,Muhammad Tariq Choudhry ,Huma Fatima Aslam ,Muhammad Ahmad (Journal of Rawalpindi Medical College, 2014)
Background : To find out incidence of extended spectrum β lactamases ( ESβLs) in multi drug resistance(MDR) Salmonella typhi. Methods: S. typhi isolates(n=342) were collected from blood culture samples. Pathogens were identified by AP1-20 E. Susceptibility was determined by using Kirby-Bauer disc diffusion method and ESBL production by double disc synergy test. Results: First line anti typhoid drugs i.e. Chloramphenical, Ampicillin and Trimethoprim/Sulfamethoxazole showed 86, 82, 80% and ciprofloxacin 52% susceptibility respectively. Sixty eight MDR S.typhi were collected during 2011 and the isolates decreased to 20 in 2012. The decrease was statistically significant (p < 0.001). Only one isolate was ESBL producer accounting (0.68 %). Conclusion: Typhoid fever is endemic throughout the year. Withdrawal of first line anti-typhoid drugs resulted in re-emerging susceptibility.Maximum cases were during hot, humid weather and minimum during cold season. MDR isolation rate decreased due to withdrawal of first line anti typhoid drugs and frequent use of third generation cephalosporins. Susceptibility of third generation cephalosporin, carbapenem and gentamycin were found to be highly effective.